TRANSFERRING COPYRIGHT OWNERSHIP OF NFT ON THE PERSPECTIVE OF POSITIVE LAW IN INDONESIA - Ruhtiani, Maya (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2023)
The development of NFT use does not function for the public’s need of objects related to copyright. In general, when someone creating NFT using another person’s work needs approval from the copyright owner. This type of normative juridical research is used as an assessment of the application of positive legal norms or legal rules applied in Indonesia. The results of research on Transferring Copyright Ownership Of NFT (Non-Fungible Tokens) On The Perspective Of Positive Law In Indonesia can be regulated by using the provisions of Article 18 UUHC related to selling-buying outright of copyrighted works which in practice must meet the requirements stated in Article 1320 of the Civil Code concerning the conditions for the validity of the agreement which are the existence of an agreement, parties’ requirement, particular objects, and lawful cause. The transaction of copyrighted works on NFT is not merely a sale and purchase for ordinary works of art, but also includes the rights to a copyrighted work protected by positive law in Indonesia. NFTs are protected under copyright laws and therefore have 2 (two) rights attached: economic and moral. In this regard, changing or distributing as well as modifying actions is included in violating moral rights. Even though the ownership has been transferred, the copyright holder must still be entitled to the economic and moral rights of the creator attached to the NFT.